High resolution DNA melting analysis: An application for prenatal control of α-thalassemia - Supatra Sirichotiyakul (2018)
Objective: To report the use of real-time gap-PCR using SYTO9 with high-resolution melting analysis (HRMA) in prenatal diagnosis of α-thalassemia 1. Materials and methods: Real-time gap-PCR using SYTO9 with HRMA was performed in 33 DNA samples from chorionic villi sampling (8 normal, 16 heterozygous, and 9 homozygous) to determine the α-thalassemia 1 gene [normal and Southeast Asia (-SEA) allele]. Result: The dissociation curve analysis in normal and -SEA allele gave a peak of Tm at 91.80 ± 0.14 °C and 88.67 ± 0.08 °C, respectively. Normal genotype and homozygous α-thalassemia 1 showed a single peak of Tm that corresponded to their alleles. The heterozygotes gave both peaks with higher normal peak and smaller -SEA peak. Thirty one samples showed consistent results with the conventional gap-PCR. Two samples with ambiguous results were confirmed to be maternal DNA contamination on real-time quantitative PCR and microsatellite assay. HRMA from both samples showed similar pattern to that of heterozygotes. However, they showed much smaller normal peak compared with the -SEA peak, which is in contrast to those of heterozygotes and can readily be distinguished. Conclusion: HRMA with SYTO9 is feasible for prenatal diagnosis of α-thalassemia. It had potential advantage of prompt detection maternal DNA contamination. Copyright © 2010 John Wiley & Sons, Ltd.